Given-that-fog-x-2x-1-x-and-g-x-5x-2-Find-f-x-

Question Number 142052 by Rankut last updated on 26/May/21
$$\boldsymbol{\mathrm{Given}}\:\boldsymbol{\mathrm{that}}\:\boldsymbol{\mathrm{fog}}\left(\boldsymbol{\mathrm{x}}\right)=\frac{\mathrm{2}\boldsymbol{\mathrm{x}}−\mathrm{1}}{\boldsymbol{\mathrm{x}}}\:\:\boldsymbol{\mathrm{and}}\:\boldsymbol{\mathrm{g}}\left(\boldsymbol{\mathrm{x}}\right)=\mathrm{5}\boldsymbol{\mathrm{x}}+\mathrm{2}, \\$$$$\boldsymbol{\mathrm{Find}}\:\:\boldsymbol{\mathrm{f}}\left(\boldsymbol{\mathrm{x}}\right). \\$$$$\\$$
Answered by iloveisrael last updated on 26/May/21
$$\Rightarrow{f}\left(\mathrm{5}{x}+\mathrm{2}\right)=\frac{\mathrm{2}{x}−\mathrm{1}}{{x}} \\$$$$\Rightarrow{f}\left(\mathrm{5}{x}+\mathrm{2}\right)=\mathrm{2}−\frac{\mathrm{1}}{{x}} \\$$$$\Rightarrow{f}\left({x}\right)=\mathrm{2}−\frac{\mathrm{1}}{\left(\frac{{x}−\mathrm{2}}{\mathrm{5}}\right)}=\mathrm{2}−\frac{\mathrm{5}}{{x}−\mathrm{2}} \\$$$$\Rightarrow{f}\left({x}\right)=\frac{\mathrm{2}{x}−\mathrm{9}}{{x}−\mathrm{2}} \\$$
Commented by Rankut last updated on 26/May/21
$${how}\:{did}\:{you}\:{get}\:\left(\frac{{x}−\mathrm{2}}{\mathrm{5}}\right) \\$$
Answered by EDWIN88 last updated on 26/May/21
$$\mathrm{f}\left(\mathrm{g}\left(\mathrm{x}\right)\right)=\mathrm{f}\left(\mathrm{5x}+\mathrm{2}\right)=\frac{\mathrm{2x}−\mathrm{1}}{\mathrm{x}} \\$$$$\:\mathrm{let}\:\mathrm{5x}+\mathrm{2}=\mathrm{u}\Rightarrow\mathrm{x}=\frac{\mathrm{u}−\mathrm{2}}{\mathrm{5}} \\$$$$\mathrm{we}\:\mathrm{get}\:\mathrm{f}\left(\mathrm{u}\right)=\frac{\mathrm{2}\left(\frac{\mathrm{u}−\mathrm{2}}{\mathrm{5}}\right)−\mathrm{1}}{\left(\frac{\mathrm{u}−\mathrm{2}}{\mathrm{5}}\right)}=\:\frac{\mathrm{2u}−\mathrm{4}−\mathrm{5}}{\mathrm{u}−\mathrm{2}} \\$$$$\:\mathrm{f}\left(\mathrm{u}\right)=\frac{\mathrm{2u}−\mathrm{9}}{\mathrm{u}−\mathrm{2}}\:\Rightarrow\:\mathrm{so}\:\mathrm{f}\left(\mathrm{x}\right)=\frac{\mathrm{2x}−\mathrm{9}}{\mathrm{x}−\mathrm{2}} \\$$
Answered by mathmax by abdo last updated on 26/May/21
$$\mathrm{fog}\left(\mathrm{x}\right)=\frac{\mathrm{2x}−\mathrm{1}}{\mathrm{5}}\:\Rightarrow\mathrm{f}\left(\mathrm{g}\left(\mathrm{x}\right)\right)=\frac{\mathrm{2x}−\mathrm{1}}{\mathrm{5}}\:\Rightarrow\mathrm{f}\left(\mathrm{5x}+\mathrm{2}\right)=\frac{\mathrm{2x}−\mathrm{1}}{\mathrm{x}} \\$$$$\mathrm{let}\:\mathrm{5x}+\mathrm{2}=\mathrm{t}\:\Rightarrow\mathrm{x}=\frac{\mathrm{t}−\mathrm{2}}{\mathrm{5}}\:\Rightarrow\mathrm{f}\left(\mathrm{t}\right)=\mathrm{2}−\frac{\mathrm{1}}{\frac{\mathrm{t}−\mathrm{2}}{\mathrm{5}}}\:=\mathrm{2}−\frac{\mathrm{5}}{\mathrm{t}−\mathrm{2}}=\frac{\mathrm{2t}−\mathrm{4}−\mathrm{5}}{\mathrm{t}−\mathrm{2}} \\$$$$=\frac{\mathrm{2t}−\mathrm{9}}{\mathrm{t}−\mathrm{2}}\:\Rightarrow\mathrm{f}\left(\mathrm{x}\right)=\frac{\mathrm{2x}−\mathrm{9}}{\mathrm{x}−\mathrm{2}} \\$$